The business and management of conventions - Poole, Barry; Weeks, Paul.; Leiper, Neil.; McCabe, Vivienne (Milton, Qld. : John Wiley and Sons, 2000)
This book is about: The business environment of conventions; The business structure of conventions; Managing suppliers to conventions; Managing human resources for conventions; ...
Keywords: Congresses; Conventions; Congresses and conventions -- Planning; Congresses and conventions -- Management